Negative Effect of Extra Voice Stimuli and Elimination of This Effect Using Hypnotic Suggestion - Kaya, Y.; Kayacan, Y.; Mor, A.; Kaya, A.S. (Editura Universitatii din Pitesti contact@efsupit.ro, 2016)
This study is realised for testing ratro of the sportmen performances which is effected by stimuli organ’s (voice) negative acts and this effected which can be decreased or not by hypnatic suggestion is realised, also If it can be decreased; the kind of stimuli and the ratio of it must be researched. This study is applied to 28 volunteer subject who were national. Before hypnosis, force application is measured with TMR EST 1000 isometric muscle training measuring equipment. During force applying, to quinea-pigs 80, 100, 110 and 120 decibels voice 1000 Hz (cih-diagmostic audiometer AS 67 (equal intensity to the ear), applied to stimuli is determined. At the second part of the study, hypnosis is applied to the same guinea-pigs and stimuli are mentioned to them. Standart suggestions were give and said tahat; when they percieved stimuli, applied forces could be increased, felt more energetic and strang. Same stimuli were applied again at the same units. Both isometric strength difference between the state and the Wilcoxon Signed Ranks Chi-Square test were analyzed using statistical method. Results were compared. In conclusion; value variation between “before hypnosis” and “after suggestion”, “during hypnosis” and “after hypnosis” were evaluated statistical. Consquently, when visual caution is given and maximum affect level is reched; at statistical there are meanful difference between hypnosis applied and not applied conditions, at auditory stimuli (80 db; p<0,001, 100 db; p<0,001, 110 db; p<0,001, 120 db; p<0,001). As a result; from this foundations and abtained findings; sportsmen concentrations are deranged by extre stimuli (it presants differenty from person to person and also different ratio), but this negative effects will be remoued by hypnotic suggestions. We must think of its curative sides of Europe, World an Olympiad medals’s color and owner this subject must be taken seriously and taken into consideration. © JPES.
Keywords: Attention; Hypnosis; Isometric Strength; Performances; Voice